Risk and suicidal ideation and its relationship with impulsivity and depression in school adolescent [Riesgo e Ideación Suicida y su Relación con la Impulsividad y la Depresión en Adolescentes Escolares] (2020)
A non-experimental cross-sectional design and explanatory study were proposed in order to analyze the statistical relationship between the suicide risk (SR) and suicidal ideation (SI) and the depression and impulsivity variables in schooling adolescents. 179 subjects (M=14.84; SD=0.82) between 14 and 17 years old participated. Variables were measured using the Plutchik Suicide Risk Scale (SRS), the Positive and Negative Suicide Ideation (PANSI) Inventory, the Beck Depression Inventory (BDI-I), and the Plutchik´s Impulsivity Scale (IS). The results show a suicide risk factor of 20.7%. Moreover, significant positive correlations (p<.001) were found among SR, negative and global SI, depression and impulsivity. The positive SI considered as a protective factor showed a negative correlation with respect to SR, the negative and global SI, depression and impulsivity. The structural equation modeling analysis applied showed depression is the mediator variable between SR, SI and impulsivity (χ2(2)=3.1; p=.212; CFI=.985; NFI=.963; TLI=.926; GFI=.987; RMSEA=.056). © 2020 AIDEP. All rights reserved.